A Systematic Review againts Risk Factors on The Low-weight Birth Incidence in Indonesia - Estri Kusumawati (Journal of Health Science and Prevention, 2017)
The number of maternal and infant mortality in Indonesia is still high. Most of Indonesian neonatal mortality occurs in the first week of life with low-weight birth (LwB) / premature as the main cause. Birth weight is an important and reliable indicator for the survival of neonates and infants, both in terms of physical growth and development of the mental status. LwB caused by many complicated factors that related each others as if maternal factors that also affect the baby's weight at their birth. The purpose of this study was to identified the determinant factors that affect the incidence of LwB based on the related research topic. The data source obtained from the scientific journals with LwB studies during the years of 2009 untill 2016 with the total of 14 studies consisting of scientific papers and thesis. In this study, researchers divided into five risk factors associated with LwB. From those factors then it divided again into 20 aspects. The result show that the maternal nutritional aspec and anemia status have become significant risk factors againts the low-weight birth incidence.